Selective psychological effects of nudging, gamification and rational information in converting commuters from cars to buses: A controlled field experiment. (May 2018) - Lieberoth, Andreas; Holm Jensen, Niels; Bredahl, Thomas
Highlights: People were given a month of free bus travel, and conversion attempted. A field experiment compared nudging, gamification and rational information. No persuasive strategy fared better than controls in terms of bus trips. Gamification proved significantly better getting participants to go online. Gamification proved significantly better at motivating intentions